The Lived Experiences Of An Undergraduate In Writing For Publication: A Narrative Inquiry - Muhammad Isa; A’thi Fauzani Wisudawati; Dian Palupi (PT. ALHAFI BERKAH INDONESIA, 2023)
Inspired by the unique of Ahmad (pseudonym), a young researcher who has successfully published his scholarly articles in international reputed journals regardless of his only holding a bachelor’s degree from a private university in East Java, this study aims to document his untold stories in writing for publication using narrative inquiry. Narrative inquiry informs the design of this investigation as the approach is particularly useful for understanding lived experiences. Findings of the current study show that through the past stories of Ahmad in his scholarly journey, he passed several events that had shaped his identity as a productive researcher with several published scholarly articles in reputable journals, namely: embarking on research world by attending academic workshops on publication, gaining good references based on interests and reading scholarly works related to them enthusiastically, finding research interests based on reading activities, preparing manuscripts, having mentorship with well-established researchers in his research interest, navigating targeted journals by browsing and reading the author’s submission guidelines and its scopes, submitting the research draft, negotiating the long revision processes. From those steps Ahmad went through in the past, reading references from reputable journals has been emphasized by him. Several issues confronted him during his journey such as difficulty in gaining access to credible references and less optimal guidance from his thesis supervisor due to her less scholarly reading activities. These barriers could be addressed by Ahmad through his virtual academic socialization with the experts of his research interest.